Germinação in vitro de sementes e morfogênese de porongo (Lagenaria siceraria (Mol.) Standl.) e mogango(Cucurbita pepo L.) - Silva, André Luís Lopes da (2005)
The establishment and germination in vitro can supply a high amount of explants to develop morphogenesis protocols necessary for flowering induction in vitro, haploid and double-haploid plant production, clonal propagation, somatic embryogenesis among other applications. The objective was to develop protocols for the establishment and germination in vitro of bottle gourd (Lagenaria siceraria (Mol.) Standl.) and squash (Cucurbita pepo L.) species to effort morphogenesis studies. Seed disinfection treatments were done with ethanol 70% and NaOCl. Seed germination in vitro was evaluated changing medium-osmotic pressure, light availability, tegument and auxin presence, imbibition s time and scarification methods. Cotyledonary explants were used to induce direct organogenesis. Apical and nodal segments were grown in MS medium without growth regulators. Bottle gourd seeds did not germinate in culture medium, but it occurred on four layers of germitest paper and distilled water in the proportion of 1:7.5 (w/w). Light is not necessary for bottle gourd seed germination. Osmotic pressure reduction did not increase bottle gourd and squash germination. Bottle gourd apical and nodal segments regenerate in culture medium without growth regulators. Cotyledonary explants of bottle gourd and squash induce aerial growth, but in a low proliferation rate